Implicit self-esteem decreases depressive symptoms, but explicit self-esteem does not: longitudinal study in Japan using the Name Letter Test - Hikaru Ohno; Akira Hasegawa (Cogent Psychology)
Studies in English-speaking countries have reported mixed findings regarding the association between implicit self-esteem assessed by the Name Letter Task and subsequent depressive symptoms. In addition, it remains uncertain whether the nature, causes and consequences of implicit self-esteem differ from those of explicit self-esteem assessed by self-report measures. The authors investigated the effects of implicit and explicit self-esteem and interactions between implicit or explicit self-esteem and negative event experiences on depressive symptoms in a non-English-speaking population. The study also examined whether experiencing positive and negative events had identical effects on implicit and explicit self-esteem. Japanese undergraduate students (N = 154) completed the Name Letter Task and scales assessing explicit self-esteem, experiences of positive and negative events, and depressive symptoms twice at an interval of 2 weeks. Results showed that baseline implicit self-esteem had a significant negative association with depressive symptoms 2 weeks later by controlling for baseline depressive symptoms. In contrast, there was no significant interaction between implicit self-esteem and experiences of negative events during the follow-up period. Baseline explicit self-esteem was not significantly related to subsequent depressive symptoms. Results also showed that experiences of positive but not negative events during the follow-up period were significantly associated with increased implicit and explicit self-esteem. These findings suggest that implicit self-esteem predicts depressive symptoms in non-selected undergraduate students and even in a non-English-speaking population. Moreover, positive event experiences might be a common cause of implicit and explicit self-esteem.